2017
DOI: 10.15850/amj.v4n2.1079
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Vitamin A Supplementation among Under-Five Children in Hegarmanah Village, Jatinangor in August 2014

Abstract: Background: The vitamin A supplementation program conducted every February and August aims to reduce children morbidity and mortality. Mother's knowledge on the importance of vitamin A is crucial to succeeding this program. This study aimed to examine the coverage of the program among under-five children and the mother's knowledge about vitamin A supplementation in Hegarmanah Village, Jatinangor in August 2014. Methods: This was a descriptive cross-sectional study involving mothers of children aged 6−59 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…the awareness campaigns in explaining the decline in coverage during the transition from the last campaign to routine VAS, as well as the positive impact on the likelihood of children benefiting from routine VAS. These findings are consistent with other studies that have shown that exposure of mothers to media sensitization on VAS, particularly through television, is associated with increased awareness and coverage of vitamin A supplementation campaigns [20][21][22]. 2.…”
Section: Discussionsupporting
confidence: 92%
“…the awareness campaigns in explaining the decline in coverage during the transition from the last campaign to routine VAS, as well as the positive impact on the likelihood of children benefiting from routine VAS. These findings are consistent with other studies that have shown that exposure of mothers to media sensitization on VAS, particularly through television, is associated with increased awareness and coverage of vitamin A supplementation campaigns [20][21][22]. 2.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it is comparable with studies conducted in Wonago district in Southern Ethiopia 59.3% [ 45 ], among twenty-three Sub-Saharan African countries 59.4% [ 38 ], and Gawadabawa district Sokoto State, Nigeria 61% [ 49 ]. However, it is lower when we compared with the studies done in Humbo district (75%) [ 33 ], Wolayita(83.1%) [ 19 ], Ghana South Dayi district(64.3%) [ 50 ], Abuja Nigeria (67%) [ 51 ], Guinea (68%) [ 52 ] , Mali (83%) [ 53 ], Bangladesh (68%) [ 12 ], (63.5%) [ 28 ], and Hegarmanah Village, Jatinangar (92.27%) [ 54 ]. The possible justification for variation may be due to differences in socio-demographic and economic characteristics, study setting, and maternal healthcare characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Analisis univariat menunjukkan balita yang tidak diberikan vitamin A yakni 51,9% lebih tinggi dibandingkan dengan balita yang diberikan vitamin yakni hanya 48,1%. Cakupan vitamin A pada penelitian ini lebih rendah dibandingkan hasil penelitian Putri et al, (2017) yang mendapatkan bahwa persentase cakupan vitamin A balita 97,27%. Hasil penelitian di Libya yang mendapatkan cakupan vitamin A pada balita 66% (Abdulmalek & Benkhaial, 2018).…”
Section: Hasil Dan Pembahasan Karakteristik Subjek Penelitianunclassified
“…Sebanyak 63,4% responden memiliki pengetahuan yang kurang tentang vitamin A, hal ini hampir sama dengan hasil penelitian Abdulmalek & Benkhaial (2018) yang menunjukkan 60% responden ibu balita memiliki pengetahuan kurang tentang vitamin A dan terdapat hubungan antara pengetahuan ibu dengan pemberian vitamin A pada balita (p value < 0,001). Penelitian di Desa Hegarmanah Jatinagor menunjukkan tinnginya pengetahuan ibu terkait suplementasi vitamin A, lebih dari separuh ibu yang pengetahuannya baik tentang supelemtansi vitamin A mendapatkan suplementasi vitamin A untuk anak balitanya (Putri et al, 2017).…”
Section: Tabel 2 Analisis Faktor Yang Berhubungan Dengan Pemberian Vunclassified